Associations between study questionnaire-assessed need and school doctor-evaluated benefit of routine health checks: an observational study - Nikander Kirsi; Hermanson Elina; Vahlberg Tero; Kaila Minna; Sannisto Tuire; Kosola Silja (BMC, 2022)
Background
In Finland, school doctors examine all children at predetermined ages in addition to annual health checks by school nurses. This study explored the association of study questionnaire-assessed need for and school doctor-evaluated benefit of routine health checks conducted by doctors.
Methods
Between August 2017 and August 2018, we recruited a random sample of 1341 children in grades 1 and 5 (aged seven and eleven years, respectively) from 21 elementary schools in four Finnish municipalities. Children mainly studying in special education groups or whose parents needed an interpreter were excluded. School nurses performed their health check as usual. Parents, nurses, and teachers then completed study questionnaires that assessed the concerns of parents, school nurses, and teachers regarding each child's physical, mental and social health. Doctors, blinded to the responses, routinely examined all the children. The primary outcome measures were (1) the need for a health check based on the study questionnaires and (2) the benefit/harm of the appointment as estimated by the doctors according to predetermined criteria, and (3) the patient-reported experience measures (PREMs) of benefit/harm of the appointment as estimated by the parents and children. We compared the need for a health check with the doctor-evaluated benefit using multilevel logistic regression.
Results
The participation rate was 75.5 %. According to all questionnaires, 20-25 % of the 1013 children had no need for a health check. The doctors regarded 410 (40.6 %) and the parents 812 (83.4 %) of the appointments as being beneficial. Respondents rarely reported harm. The children who were classified as needing a health check more often benefitted from the health check (assessed by the doctor) than children with no need for one (OR 3.53; 95 % CI 2.41-5.17).
Conclusions
The need for a health check is an important predictor of school-doctor evaluated benefit of the health check. This approach could allow school doctors to allocate time for the children who need them most.